CIRCULAR ECONOMY FROM PERSPECTIVE OF WASTE MANAGEMENT TRENDS IN EU - Slavka Šagátová; Denisa Gajdová (Trendy v podnikání)
Reducing the environmental burden of production activities is an essential part of global efforts to ensure sustainable development. Achieving this trend requires effective resource management and waste handling, which are integral components of the circular economy. Successful waste management largely depends on understanding the causes of waste generation. This article focuses on examining the relationships between waste production, gross domestic product (GDP), and material consumption in European Union (EU) countries, with the aim of identifying waste management trends and highlighting the most high-risk economic sectors in this context. The research involved gathering data on the volume of waste produced by type and economic sector, GDP, and material consumption in individual EU member states over a nine-year period. Based on this data, a correlation and regression analysis was conducted to explore the interrelationships among these factors. The analysis examines whether more economically developed countries can manage waste more effectively, and identifies differences in waste production across various sectors. It also identifies the largest contributors to the overall volume of waste generated in individual EU countries. The research findings also allow for the identification of existing relationships between waste production and material consumption in different countries. These insights provide crucial information for the development of environmental policies and strategies that support sustainable economic growth and environmental protection in EU countries.